Pergeseran Politik Hukum Zakat dari Era Soekarno Menuju Soeharto - Muhamad Nasrudin (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2018)
Regarding Indonesia as non-islamicstate, discourse of almsgiving management is very important to be discussed. Islam tends to argue that The State has to manages almsgiving. But in other hand, NKRI as non-islamicstate tends to avoiding intervention in religious practical event. When Soekarno taok rules, national revolution gave full attention, so the dinamics of almsgiving management has no intention. But when Soeharto took rules, intention to The State to manage almsgiving get bigger number. In other hand, The State gave counter-attack, the best it can. Based on bibliotical research, this paper displays the dinamics of almsgiving management law-policy in those eras and describes how far the shift was happened. Kata kunci: politik hukum zakat, pengelolaan zakat, UU Pengelolaan Zakat,